2002
DOI: 10.2514/3.15257
|View full text |Cite
|
Sign up to set email alerts
|

Local time-stepping algorithm for solving probability density function turbulence model equations

Abstract: A local time-stepping algorithm has been developed to improve the numerical ef ciency of Lagrangian particlebased Monte Carlo methods for obtaining the steady-state solutions of the modeled probability density function equations of turbulent reacting ows. On each step in the pseudo-time-marching algorithm, the properties of each particle are advanced by a time step, the magnitude of which depends on the particle's spatial location. This algorithm has been incorporated into the consistent hybrid nite volume/par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…It has been shown that the consistent hybrid method is computationally more efficient than the best available alternative solution technique by a factor of an order of magnitude or more [2,6]. The numerical efficiency of the hybrid algorithm is further improved by the recent development of a local time stepping algorithm that has been shown to accelerate the global convergence of the hybrid method as much as by a factor of 10 depending on grid stretching [7]. Combined with the local time stepping algorithm, the consistent hybrid method thus makes the PDF methodology a feasible design tool for the practical applications in engineering or elsewhere.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been shown that the consistent hybrid method is computationally more efficient than the best available alternative solution technique by a factor of an order of magnitude or more [2,6]. The numerical efficiency of the hybrid algorithm is further improved by the recent development of a local time stepping algorithm that has been shown to accelerate the global convergence of the hybrid method as much as by a factor of 10 depending on grid stretching [7]. Combined with the local time stepping algorithm, the consistent hybrid method thus makes the PDF methodology a feasible design tool for the practical applications in engineering or elsewhere.…”
Section: Introductionmentioning
confidence: 97%
“…In this code, the particle algorithm is largely based on the PDF2DV [25] code and the FV algorithm is a slight modification of the alternating direction implicit (ADI) scheme of Caughey [26]. The local time stepping algorithm that has been recently developed and shown to significantly accelerate the global convergence of the hybrid method [7] is also incorporated into the present hybrid method. Note that a similar local time stepping procedure has been recently presented by Mobus et al [27] for convergence acceleration of Lagrangian PDF methods.…”
Section: Numerical Solution Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to ensure second-order accuracy, the 'midpoint rule' is used [13,14]. A local time-stepping algorithm developed in the framework of statistically stationary problems [15] is applied.…”
Section: Turbulence Heat and Mass Transfermentioning
confidence: 99%
“…The Cartesian grid used for the computations consists of 120 cells in axial direction and 64 cells in the radial direction. A local time-stepping algorithm for the gas phase as well as for the dispersed phase was used to determine the time step used in each cell [15,17]. For the dispersed phase, five particles per class per cell were used and 13 droplet classes were considered.…”
Section: Application To a Turbulent Two-phase Jet: Configuration And mentioning
confidence: 99%